Neutral pion and [eta] meson production in p-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; et al. (The European physical journal. C, Particles and fields, 2018)
Neutral pion and ηη\eta meson invariant differential yields were measured in non-single diffractive p-Pb collisions at sNN−−−√sNN\sqrt{s_{\mathrm{NN}}} = 5.02 TeV with the ALICE experiment at the CERN LHC. The analysis combines results from three complementary photon measurements, utilizing the PHOS and EMCal calorimeters and the Photon Conversion Method. The invariant differential yields of π0π0\pi ^{0} and ηη\eta meson inclusive production are measured near mid-rapidity in a broad transverse momentum range of 0.3<pT<20 GeV/c0.3<pT<20 GeV/c0.3< p_{\mathrm{T}} < 20 \hbox { GeV}/c and 0.7<pT<20 GeV/c0.7<pT<20 GeV/c0.7< p_{\mathrm{T}} < 20\hbox { GeV}/c, respectively. The measured η/π0η/π0\eta /\pi ^{0} ratio increases with pTpTp_{\mathrm{T}} and saturates for pTpTp_{\mathrm{T}} > 4 GeV/cGeV/c\hbox {GeV}/c at 0.483±0.015stat±0.015sys0.483±0.015stat±0.015sys0.483 \pm 0.015_{\mathrm{stat}} \pm 0.015_{\mathrm{sys}}. A deviation from mTmTm_{\mathrm{T}} scaling is observed for pT<pT<p_{\mathrm{T}}< 2 GeV/cGeV/c\hbox {GeV}/c. The measured η/π0η/π0\eta /\pi ^{0} ratio is consistent with previous measurements from proton-nucleus and pp collisions over the full pTpTp_{\mathrm{T}} range. The measured η/π0η/π0\eta /\pi ^{0} ratio at high pTpTp_{\mathrm{T}} also agrees within uncertainties with measurements from nucleus-nucleus collisions. The π0π0\pi ^{0} and ηη\eta yields in p-Pb relative to the scaled pp interpolated reference, RpPbRpPbR_{{\mathrm{pPb}}}, are presented for 0.3<pT<0.3<pT<0.3 < p_{\mathrm{T}}< 20 GeV/cGeV/c\hbox {GeV}/c and 0.7<pT<0.7<pT<0.7 < p_{\mathrm{T}}< 20 GeV/cGeV/c\hbox {GeV}/c, respectively. The results are compared with theoretical model calculations. The values of RpPbRpPbR_{{\mathrm{pPb}}} are consistent with unity for transverse momenta above 2 GeV/cGeV/c\hbox {GeV}/c. These results support the interpretation that the suppressed yield of neutral mesons measured in Pb-Pb collisions at LHC energies is due to parton energy loss in the hot QCD medium.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V.J.G. Feuillard, P. Glässel, J. Kim, M.K. Köhler, S. Klewin, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel wird "eta" als griechischer Buchstabe dargestellt
Gesehen am 04.07.2019